2014
DOI: 10.1242/jcs.154732
|View full text |Cite
|
Sign up to set email alerts
|

Midbody remnant engulfment after cytokinesis abscission in mammalian cells

Abstract: BSTRACTThe midbody remnant (MBR) that is generated after cytokinetic abscission has recently attracted a lot of attention, because it might have crucial consequences for cell differentiation and tumorigenesis in mammalian cells. In these cells, it has been reported that the MBR is either released into the extracellular medium or retracted into one of the two daughter cells where it can be degraded by autophagy. Here, we describe a major alternative pathway in a variety of human and mouse immortalized cells, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
110
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(125 citation statements)
references
References 66 publications
(140 reference statements)
11
110
1
3
Order By: Relevance
“…Surprisingly, remnants can be exchanged between sister and even non-sister cells. Thus, our study published in Journal of Cell Science changed the understanding of how remnants are inherited and degraded in mammalian cells, by suggesting a mechanism of how remnants signal over long distances between cells (Crowell, et al, 2014).…”
Section: Elizabeth Crowellmentioning
confidence: 97%
See 2 more Smart Citations
“…Surprisingly, remnants can be exchanged between sister and even non-sister cells. Thus, our study published in Journal of Cell Science changed the understanding of how remnants are inherited and degraded in mammalian cells, by suggesting a mechanism of how remnants signal over long distances between cells (Crowell, et al, 2014).…”
Section: Elizabeth Crowellmentioning
confidence: 97%
“…This discovery was explored further by using cell biology techniques, and revealed that midbody engulfment occurs in all cell lines tested (Crowell, et al, 2014), and in collaboration with the biophysicist Jean-Yves Tinevez, which permitted to simulate midbody turnover in a dynamic cell population (Crowell, et al, 2013). Now living in Normandy, Elizabeth is pursuing her scientific career in the private sector, with emphasis on the bio-informatics field.…”
Section: Elizabeth Crowellmentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, the structure could be internalized into autophagosomes directly, released into the extracellular milieu, or the particle could be later phagocytosed by the dividing cell or its neighbors and ultimately degraded by lysosomal processes (Crowell et al 2014). The balance between these fates varies in a cell type -dependent manner (Ettinger et al 2011).…”
Section: Fate Of Midbody Remnantsmentioning
confidence: 99%
“…The balance between these fates varies in a cell type -dependent manner (Ettinger et al 2011). Division remnants have been suggested to alter cellular behavior (Ettinger et al 2011;Kuo et al 2011), but the perturbations used to alter the fate of internalized midbodies might have indirect effects (Crowell et al 2014). …”
Section: Fate Of Midbody Remnantsmentioning
confidence: 99%